Short-duration phase-change material cryotherapy selectively enhances early neuromuscular and perceptual recovery - Chong Gang; Hao Wang; Yujue Wang; Yongsheng Lan (PLoS ONE, 2026)
The purpose of this study was to examine whether short-duration phase-change material cooling (PCM) applied at different temperatures influences acute recovery following fatigue induced by stretch–shortening cycle exercise (SSC). Sixty-four physically active participants were randomly assigned to 5°C, 10°C, or 15°C PCM cryotherapy group or a passive recovery control group. After completing a SSC fatigue protocol, participants underwent a 15-minute PCM intervention, and peak torque (PT), mean power, rate of force development (RFD), countermovement jump (CMJ) performance, Rating of perceived exertion (RPE), modified endurance ratio (MER), vastus lateralis (VL) and Rectus Femoris (RF) stiffness were assessed immediately after fatigue (Imm-fatigue), immediately after PCM cryotherapy (Imm-PCM), and 60 minutes post PCM cryotherapy (Post60-PCM). Mean power and RFD were significantly greater in PCM groups compared with the control group at Imm-PCM (P ≤ 0.01), with mean power remaining elevated in the 15°C PCM group at post-60-PCM (P ≤ 0.05). RPE was significantly lower in all PCM groups at Imm-PCM and post60-PCM compared with control (P ≤ 0.01). No between-group differences were observed for PT, CMJ, MER, or muscle stiffness, and no temperature-dependent effects were detected within the 5–15 °C. These findings indicate that 15-minute PCM cryotherapy selectively accelerates early-phase neuromuscular and perceptual recovery without affecting maximal strength, endurance capacity, or passive muscle mechanical properties. From an applied perspective, PCM cryotherapy may be an effective strategy to enhance explosive performance and perceived readiness during short recovery intervals in training or competition settings.